Improved plasmids for gene targeting at the his-3 locus of Neurospora crassa by electroporation: Correction - B S Margolin; M Freitag; E U Selker (Fungal Genetics Reports, 2000)
Two mistakes in our article on gene replacement by gene targeting at the his-3 locus (Margolin, B.S. et al., 1997, FGN 44:34-36) have come to our attention.